5kW High peak power, 0.2 mJ high pulse energy, linearly-polarized pulsed laser from a single all-fiber oscillator. (December 2015) - Shi, Chen; Huang, Long; Wang, Xiaolin; Zhou, Pu
Abstract: We report a high peak power ytterbium-doped fiber laser that emitted linearly-polarized laser at 1064 nm. An intracavity polarization-maintaining (PM) acousto-optic modulator (AOM) was used as a Q-switch to generate pulsed laser output. The whole system was constructed with all-fiber structure. The power of the polarized laser reached 4.21 W and a polarization purity of greater than 97.6% under the repetition rate of 20 kHz. The pulse width was 37 ns, which implied a 5 kW peak power and 0.2 mJ pulse energy. It is the highest peak power output from a linearly-polarized, Q-switched fiber laser oscillator to the best of our knowledge. Highlights: We constructed a linearly-polarized pulsed all fiber oscillator. We achieved 5 kW peak power and 0.2 mJ pulse energy output. The oscillator has the potential for further power scaling. Intracavity round trip gain was calculated to estimate Raman gain.